DYSLIPIDEMIC FEMALES HAVE EQUAL RISK TO CARDIAC DISEASES AS MALES - A NEUTROPHIL MEDIATED PATHWAY. - N.KARTHICK,; K.N.Poornima,; K.Dilara,; Kumar, G.Thilip; A.Saravanan, (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Coronary artery disease (CAD) is one of the leading cause of death in adult women. Dyslipidemia is one of the major risk factor for CAD and it further causes proliferation of neutrophils and monocytes. Neutrophil is the hall mark for inflammation and involve in the development of early atherogenesis. The objective of the current study is to evaluate the effect of dyslipidemia on neutrophil count in dyslipidemic male and female. Methods: The study group included 49 patients with dyslipidemia and 49 age and sex matched healthy controls. The lipid profile and various hematological parameters were estimated. Result: Total leucocyte and neutrophil count is significantly increased in dyslipidemic patients and there is no significant difference between male and female dyslipidemic subjects, both are equally affected. Conclusion: The study concludes that rise in neutrophil count in dyslipidemic subjects is an additional risk for early atherosclerotic lesions and coronary artery disease. Keywords: Dyslipidemia, Neutrophil, Coronary artery disease (CAD)